Pengaruh Penggunaan Media Belajar dan Minat Belajar terhadap Hasil Belajar Matematika (Eksperimen pada Siswa Kelas XI IPA SMA Negeri 8 Kota Tangerang Selatan Tahun Pelajaran 2010 / 2011) - Tatan Zenal Mutakin; Teti Sumiati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2011)
The research is an experiment conducted in SMA Negeri 8 Tangerang City, Banten, on the influence of learning and use of media interest in learning of mathematics learning outcomes. The purpose of this study was to analyze the influence of media use to learn and interest in learning mathematics learning outcomes. (Experiment In Student Class XI IPA SMAN 8 Tangerang City Year Lesson 2010/2011). The research method used is an experimental method using the technique "factor analysis" with "Two Way Anova", aided by SPSS version 15.0. The results of the analysis studies suggest that: 1) There is the media's influence on the learning outcomes of mathematics learning, 2) There is interest in studying the influence on the results of studying mathematics, and 3) There is no interaction between the learning outcomes of students with interest in learning mathematics students.